Ask top 10 questions to solve retention challenges. Issue 5 (18th July 2018) - Hope, Joan
Abstract : ORLANDO — Data can provide a wealth of information about how to retain students. But to get the best answers, you have to ask good questions. Brian Galloway, director of student retention services at Villanova University; and Daniel McDevitt, director of student success and first year experience at Saint Joseph's University, explained the top 10 questions you should ask when you review your data at a session at the American Association of Collegiate Registrars and Admissions Officers annual conference.